Organic Fertilization and Tree Orchards - Theocharis Chatzistathis; Victor Kavvadias; Thomas Sotiropoulos; Ioannis E. Papadakis (Agriculture, 2021)
Organic fertilization has been proposed as an alternative approach to supply nutrients for crops, in the frame of organic and sustainable agriculture, with the aim to decrease high inorganic fertilization rates, protect the environment and decrease production costs for farmers. Since different types of organic fertilizers, such as manures, olive mill wastewater (OMW), sewage sludge (SS), crushed pruning wastes, composts and cover crops, exist as soil amendments to improve soil fertility, enhance plant nutrition and sustain the productivity of tree crops, their role as biofertilizers has been fully analyzed under the most important published papers. In addition, the benefits and drawbacks of organic fertilization, in a comparative approach with inorganic fertilization, are presented and discussed. Within the most important advantages of organic fertilizers, the enhancement of beneficial soil microorganisms and the improvement in soil physical properties and fertility should be included, while their most important disadvantage is their inability to directly satisfy the prompt N nutritional needs of tree crops, due to slow N mineralization rates. Finally, some novel aspects on the interrelation among innovative organic fertilizers for tree crops, sustainable field management, crop productivity and fruit quality are also included in this review, under the light of the most important and recent research data existing in the literature, with the aim to provide recommendations and future directions for organic fertilizers by tree growers.